Development of B1 Level Listening Learning Media Using the Proprofs Platform - Maya Aristia; Risnovita Sari (Asian Journal of Applied Education (AJAE), 2024)
This research was carried out in the library of the Faculty of Language and Arts, Medan State University to develop learning media for B1 listening practice using the Proprofs platform. The development model used in this research is the Richey and Klein development model. The stages are: (1) planning stage, (2) manufacturing stage, and (3) evaluation stage. The focus of this research comes from the problems experienced by students majoring in German when listening to B1 level, namely lack of mastery of vocabulary. Vocabulary based on the themes Generationen, Migration and Europe will be developed in this research. The data source for this research is the book Studio Express B1 (Funk, et al, 2018) pages 90 to 114. The research results are in the form of learning media for listening practice in the form of online quizzes accompanied by audio and video. There are 20 questions for each topic that come from audio and video. The types of questions are incomplete sentences, multiple choice and true or false. The media created is validated by media experts, with a score of 95 (very good).